Synthesis and characterization of soluble seco-porphyrazines with bulky substituents - Gonca, Erguen; Keskin, Bahadir (TAYLOR & FRANCIS LTD, 2009)
By cyclotetramerization of 3,4-bis(4-tert-butylphenyl)pyrroline-2,5-diimine in the presence of magnesium butanolate, magnesium porphyrazinate with eight (4-tert-butylphenyl) units on the periphery has been synthesized. Its demetalation by the treatment with trifluoroacetic acid resulted in a partially oxidized product, namely, octakis(4-tert-butylphenyl)-2-seco-porphyrazine-2,3-dione. Further reaction of this product with copper(II) acetate, zinc(II) acetate, and cobalt(II) acetate led to the metallo derivatives, [octakis(4-tert-butylphenyl)-2-seco-2, 3-dioxoporphyrazinato]M(II) (M = Cu, Zn, Co). These soluble complexes have been characterized by elemental analysis, FT-IR, 1H NMR, UV-Vis, and mass spectral data.
Keywords: Seco-porphyrazine; 4-Tert-butylphenyl; Pyrroline; Copper; Zinc; CATIONIC PORPHYRINS; DERIVATIVES; ASSEMBLIES; MAGNESIUM; MOIETIES; BRIDGES; Chemistry